Association of Matrix Metalloproteinase 9 and Cellular Fibronectin and Outcome in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Wang, Lu; Deng, Linghui; Yuan, Ruozhen; Liu, Junfeng; Li, Yuxiao; Liu, Ming (Frontiers in Neurology, 2020)
Introduction: The role of matrix metalloproteinase 9 (MMP-9) and cellular fibronectin (c-Fn) in acute ischemic stroke is controversial. We systematically reviewed the literature to investigate the association of circulating MMP-9 and c-Fn levels and MMP-9 rs3918242 polymorphism with the risk of 3 outcome measures after stroke. Methods: We searched English and Chinese databases to identify eligible studies. Outcomes included severe brain edema, hemorrhagic transformation, and poor outcome (modified Rankin scale score ≥3). We estimated standardized mean differences (SMDs) and pooled odds ratios (ORs) with 95% confidence intervals (CIs). Results: Totally, 28 studies involving 7239 patients were included in the analysis of circulating MMP-9 and c-Fn levels. Meta-analysis indicated higher levels of MMP-9 in patients with severe brain edema (SMD 0.76, 95%CI 0.18 to 1.35, 4 studies, 419 patients) and hemorrhagic transformation (SMD 1.00, 95%CI 0.41 to 1.59, 11 studies, 1709 patients) but not poor outcome (SMD 0.30, 95%CI -0.12 to 0.72, 4 studies, 759 patients). Circulating c-Fn levels were also significantly higher in patients with severe brain edema (SMD 1.55, 95%CI 1.18 to 1.93, 4 studies, 419 patients), hemorrhagic transformation (SMD 1.75, 95%CI 0.72 to 2.78, 4 studies, 458 patients), and poor outcome (SMD 0.46, 95%CI 0.16 to 0.76, 2 studies, 210 patients). Meta-analysis of 3 studies indicated that the MMP-9 rs3918242 polymorphism may be associated with hemorrhagic transformation susceptibility under the dominant model (TT + CT versus CC: OR 0.621, 95%CI 0.424 to 0.908, P=0.014). No studies reported the association between MMP-9 rs3918242 polymorphism and brain edema or functional outcome after acute stroke. Conclusion: Our meta-analysis showed that higher MMP-9 levels were seen in stroke patients with severe brain edema and hemorrhagic transformation but not poor outcome. Circulating c-Fn levels appear to be associated with all 3 outcomes including severe brain edema, hemorrhagic transformation, as well as poor functional outcome. The C-to-T transition at the MMP-9 rs3918242 gene appears to reduce the risk of hemorrhagic transformation.